PERANAN KEPALA DESA DALAM PARTISIPASI PENGGERAKAN PEMBANGUNAN DI DESA SALIBABU KECAMATAN SALIBABU KABUPATEN KEPULAUAN TALAUD - pinggian, Yulia; Mandey, JANTJE; Pombengi, Jericho D (Sam Ratulangi University, 2015)
ABSTRACKThe implementation of the duties and functions of a village chief in the government isone of the activities of government officials in an effort to improve the welfare of thecommunity, as the purpose of this study is to provide a description of the implementation ofthese functions. The role of village chief is very important in approaching and grow and developself-help mutual aid society in order to realize the implementation of development that has beenplanned in the Budget of the Village.This means that the head of the village as a leader in thevillage is the organizer and the person in charge in the field of governance and communitydevelopment, as well as village chief is responsible for growing and developing self-help mutualaid society. By looking at how important the role of the village head held thus further researchon